(untitled) (Research, Society and Development, 2020)
The aim of this study was to analyze the knowledge and attitudes of pregnant women in the city of Natal / RN, about their oral health during pregnancy and the oral health care that should be taken with the baby. In the period from October 2013 to March 2014, a questionnaire adapted for pregnant women, aged between 18 and 39 years, from 04 Family Health Unit, information on maternal education, basic aspects of prenatal care, was applied. as well as oral health care and, lastly, aspects about dental care for babies. The data were analyzed using the X2 test with a 5% significance level, using the Mann-Whitney and Kruskal-Wallis tests. The absolute and percentage frequency was also used to describe the socioeconomic and demographic variables. In this study, mothers with twelve or more years of study (40%) prevailed. It was found that the majority (93.8%) had a family income less than or equal to three minimum wages and that when the survey was conducted, 84.6% had already had 06 or more prenatal consultations. The pregnant women did not direct their knowledge of oral health, the importance given to visiting the dentist during pregnancy, considering that among those who have 12 years or more of study, the majority (15.4%), did not know about this ability (p ˂0.5). Women who have undergone guidance on breastfeeding, on the importance of breastfeeding, and on oral habits such as the use of a pacifier or digital suction are harmful (p˂0.5). Considering the care they reported adopting with oral health and that of the baby, it is concluded that pregnant women did not show concern for oral health care, evidenced by the lack of knowledge.